PERNAK-PERNIK FUNGSIONAL DARI KORAN BEKAS SEBAGAI PELUANG USAHA DI MASA PANDEMI COVID-19 - Andaiyani, Sri; Hidayat, Ariodillah; Adnan, Nazeli; yunisvita, yunisvita (LPPM Univ. Ibn Khaldun Bogor, 2022)
The Covid-19 pandemic demands that people think creatively and see business opportunities that exist. The community can take advantage of inorganic waste that can be recycled and easily obtained, such as used newspapers. This is what motivates the implementation team for community service activities of Sriwijaya University to provide training in making handicrafts from newsprint. This activity was attended by 40 housewives and young women in Kerinjing Village, Tanjung Raja District, Ogan Ilir Regency. The method of implementing this activity is training. The stages of implementation include the delivery of material, discussion and practice. With the enthusiasm and enthusiasm of the participants, this activity was carried out successfully. All participants are proficient in making newspaper coverage as a basis for making products. About 85 percent of the participants succeeded in making coasters and pencil holders. Meanwhile, only about 35 percent of the participants made flower pots and fruit baskets. Thus, the participants have been able to turn used newspaper waste into a product with sale value.